Desain Sprayer Pertanian dengan Sel Surya - Rahmadani, Didik; , Aris Budiman, S.T., M.T; , Hasyim Asy'ari, ST.MT (2015)
The last few years this energy is a crucial issue in the world. Increased energy demand caused by population growth and resource depletion of world oil reserves as well as problems of emissions from fossil fuels put pressure on any country to immediately use of renewable energy and alternative energy. Research and preparing reports Agricultural Sprayer Design with Solar Cells made within two weeks. In the study there are obstacles that erratic weather, so the research time becomes longer than the schedule that has been made sebelumnya.Tempat research performance Agricultural Sprayer Design with Solar Cells Punduhsari Village, District Manyaran, Wonogiri. Precisely in the fields owned by Mr. Rusdianto. Data collection was performed 6 times with different light intensities. Testing characteristics of solar cells based on the intensity of solar power generated, among others: (1) The voltage and current generated by solar cells; (2) The intensity of solar power generated by solar cells; (3) Resilience battery obtained when testing. Tests conducted by the author says that when the light intensity of 0 or when not using solar cells, able to turn the sprayer for 35.87 minutes. When not using the full power of solar cells supplied by the battery. As for the highest intensity that is obtained when the study is 100,100 lux, able to turn the sprayer for 59.41 minutes. solar cells can supply the battery by 65.62% so that the sprayer can work longer.